Epilepsy disrupts hippocampal phase precision and impairs working memory. Issue 10 (22nd July 2022) - Arski, Olivia N.; Wong, Simeon M.; Warsi, Nebras M.; Pang, Elizabeth; Kerr, Elizabeth; Smith, Mary Lou; Taylor, Margot J.; Dunkley, Benjamin T.; Ochi, Ayako; Otsubo, Hiroshi; Sharma, Roy; Yau, Ivanna; et al.
Abstract: Objective: Working memory deficits are prevalent in childhood epilepsy. Working memory processing is thought to be supported by the phase of hippocampal neural oscillations. Disruptions in working memory have previously been linked to the occurrence of transient epileptic activity. This study aimed to resolve the associations between oscillatory neural activity, transient epileptiform events, and working memory in children with epilepsy. Methods: Intracranial recordings were acquired from stereotactically implanted electrodes in the hippocampi, epileptogenic zones, and working memory‐related networks of children with drug‐resistant epilepsy during a 1‐back working memory task. Interictal epileptic activity was captured using automated detectors. Hippocampal phase and interregional connectivity within working memory networks were indexed by Rayleigh Z and the phase difference derivative, respectively. Trials with and without transient epileptiform events were compared. Results: Twelve children (mean age = 14.3 ± 2.8 years) with drug‐resistant epilepsy were included in the study. In the absence of transient epileptic activity, significant delta and theta hippocampal phase resetting occurred in response to working memory stimulus presentation (Rayleigh z‐score = 9, Rayleigh z‐score = 8). Retrieval trials that were in phase with the preferred phase angle were associated with faster reaction times ( p = .01, p = .03). Concurrently, delta and theta coordinated interactions between the hippocampi and working memory‐related networks were enhanced (phase difference derivative [PDD] z ‐scores = 6–11). During retrieval trials with pre‐encoding or pre‐retrieval transient epileptic activity, phase resetting was attenuated (Rayleigh z‐score = 5, Rayleigh z‐score = 1), interregional connectivity was altered (PDD z ‐scores = 1–3), and reaction times were prolonged ( p = .01, p = .03). Significance: This work highlights the role of hippocampal phase in working memory. We observe poststimulus hippocampal phase resetting coincident with enhanced interregional connectivity. The precision of hippocampal phase predicts optimal working memory processing, and transient epileptic activity prolongs working memory processing. These findings can help guide future treatments aimed at restoring memory function in this patient population.